2015
DOI: 10.1371/journal.pone.0128943
|View full text |Cite
|
Sign up to set email alerts
|

PRR11 Is a Prognostic Marker and Potential Oncogene in Patients with Gastric Cancer

Abstract: PRR11 is a potential candidate oncogene that has been implicated in the pathogenesis of lung cancer, however the role of PRR11 in gastric cancer is currently unclear. In the present study, we investigated the role of PRR11 in gastric cancer by evaluating its expression status in samples from a cohort of 216 patients with gastric cancer. PRR11 was found to be overexpressed in 107 (49.5%) patients by immunohistochemistry of tissue microarrays generated using the patient samples. Furthermore, PRR11 overexpression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
43
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 24 publications
4
43
0
2
Order By: Relevance
“…Through regulating important genes involved in cell cycles and tumorigenesis, PRR11 participates in the initiation and progression of lung cancer and epithelial-to-mesenchymal transition in breast cancer [11]. Our previous research showed that PRR11 widely activated in human gastric cancer, and was an independent prognostic factor for gastric cancer patients, which are consistent with the hypothesis that PRR11 functions as an oncogene in the development and progression of gastric cancer [12]. However, whether an increase in PRR11 expression is responsible for the expansion of gastric CSC populations is not known.…”
Section: Introductionsupporting
confidence: 79%
See 3 more Smart Citations
“…Through regulating important genes involved in cell cycles and tumorigenesis, PRR11 participates in the initiation and progression of lung cancer and epithelial-to-mesenchymal transition in breast cancer [11]. Our previous research showed that PRR11 widely activated in human gastric cancer, and was an independent prognostic factor for gastric cancer patients, which are consistent with the hypothesis that PRR11 functions as an oncogene in the development and progression of gastric cancer [12]. However, whether an increase in PRR11 expression is responsible for the expansion of gastric CSC populations is not known.…”
Section: Introductionsupporting
confidence: 79%
“…Real-time quantitative PCR reaction was performed using SYBR1 Premix Ex TaqTM kit (Takara, Kyoto, Japan) according to the manufacturer's instructions and conventional PCR assays were performed using previously described method [12]. GAPDH was used as an internal standard.…”
Section: Rna Extraction and Real-time Pcrmentioning
confidence: 99%
See 2 more Smart Citations
“…Specific short hairpin RNA-mediated depletion of PRR11 causes cell cycle arrest, leading to a significant decrease in cell viability [7]. PRR11 has been regarded as a potential new target for the diagnosis and treatment of lung cancer, as it regulates key genes associated with tumor occurrence [8,9]. However, despite growing evidence demonstrating that PRR11 is as an important cancer-related protein, the role of PRR11 in OC and the underlying molecular mechanisms have not been investigated.…”
Section: Introductionmentioning
confidence: 99%